2000
DOI: 10.1007/s001250051537
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypertriglyceridaemia in Type II diabetes: involvement of apoC-III Sst-I polymorphism, LPL mutations and apo E3 deficiency

Abstract: Hypertriglyceridaemia and reduced HDL-cholesterol concentrations are the prominent features of the atherogenic dyslipaemia commonly observed in insulin-resistance states [1,2] and Type II (non-insulin-dependent) diabetes mellitus [3±6]. Severe hypertriglyceridaemia is not uncommon in Type II diabetes [7,8] but its prevalence and mechanism are not clearly established. Mild hypertriglyceridaemia in Type II diabetes is dependent upon glucose control and nutritional factors such as intake of carbohydrates and alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Most humans with diabetes do not have marked hypertriglyceridemia. However humans, like mice, that have a defect in LpL regulation are most likely to develop severe hypertriglyceridemia with diabetes 60, 62,63. On the other hand, humans with robust LpL activity are likely to be protected from hypertriglyceridemia regardless of their degree of insulin deficiency or resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Most humans with diabetes do not have marked hypertriglyceridemia. However humans, like mice, that have a defect in LpL regulation are most likely to develop severe hypertriglyceridemia with diabetes 60, 62,63. On the other hand, humans with robust LpL activity are likely to be protected from hypertriglyceridemia regardless of their degree of insulin deficiency or resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted as described (5). Prior to direct sequencing of the APOA5 (nt -25 to +1820), genomic DNA (0.2 µg) was subjected to PCR with the 2 primers APOA5gF1 (5′-CAGGT-GGGCAGGGGAGAGGTGGTA-3′) and APOA5gR1 (5′-ATGGCAGCCCT-GGGGAGACAAGTG-3′) generating a 2526-bp product.…”
Section: Apoa5 Genomic Sequence Analysismentioning
confidence: 99%
“…Severe hypertriglyceridemia (HTG) is a general condition with a few well-documented genetic contributors, including lipoprotein lipase (LPL), APOC2, and APOE, as well as environmental factors such as diet and/or conditions such as pregnancy and diabetes (2)(3)(4)(5). While genetic factors account for a large proportion of the rare type 1 hyperlipidemia, the complex interaction between genetics and environment is only partly understood in the more common type 5 hyperlipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…In T2DM, LPL activity is commonly deficient and contributes to the increased level of serum TGs and the decreased level of HDL (Taskinen, 1987;Klannemark et al, 2000;Kalmar et al, 2005). Several studies have shown an association between genetic variations in LPL and lipid metabolism in T2DM patients (Marcais et al, 2000;Ma et al, 2003;Socquard et al, 2006). For example, an association between higher plasma TGs and lower HDL cholesterol levels and the H+ allele of LPL HindIII polymorphism has been reported in Chinese patients with early-onset T2DM (Ma et al, 2003).…”
Section: Introductionmentioning
confidence: 99%